Effect of orofacial myofunctional therapy along with preformed appliances on patients with mixed dentition and lip incompetence - Xue Yang; Guangyun Lai; Jun Wang (BMC, 2022)
Abstract Background Various preformed early orthodontic appliances for correcting oral habits and training orofacial muscles have emerged on the market. However, there are few reports on the effectiveness of these appliances for orofacial myofunctional training. Methods This retrospective study evaluated children with lip incompetence and mixed dentition treated at the Pediatric Dentistry Department of Shanghai Ninth People's Hospital from 2016 to 2018. A total of 109 children (54 males, 55 females; age range: 7-10 years, mean age: 8.2 years) were selected from an overall sample of 870 patients. During the first visit, all patients were instructed to perform active lip and tongue training at home daily and were divided into two groups according to the kind of appliances worn. The first group consisted of 56 subjects (30 females; 26 males), with a mean age of 8.1 years (SD 1.1 years), treated with preformed appliances. The second group consisted of 53 subjects (25 females; 28 males), with a mean age of 8.2 years (SD 1.0 years), treated with conventional early orthodontic appliances (arch expansion devices along with "2*4" local fixed appliances). For each subject in the two groups, initial (pretreatment, T1) and final (posttreatment, T2) intraoral and external photos, dental casts, lateral cephalograms, and orthopantograms were taken, and lip strength was measured. SNA, SNB, ANB, APDI, FMA, U1SN, and IMPA before and after treatment were measured by The Dolphin Imaging Cephalometric Analysis Software. The hyoid bone position was also recorded. Differences between groups were identified with an independent sample t-test (P < 0.05). Results In the first group, a statistically significant forward movement of the mandible was detected by an increase in SNB of − 1.06 degrees (P < 0.01) and an increase in APDI of − 2.23 degrees (P < 0.01). The increase in IMPA (− 3.21 degrees, P < 0.01) demonstrated a statistically significant protrusion of the lower incisors. Lip strength significantly increased (− 2.44, P < 0.01). The increase in HC3 (− 1 mm, P < 0.01) and HFH (− 2.95 mm, P < 0.01) implied a forward and downward movement of the hyoid bone. In the second group, a statistically significant forward movement of the mandible was also detected by an increase in APDI of -1.96 degrees (P < 0.01). Lip strength also significantly increased (− 1.24, P < 0.01). The increase in HFH (− 2.55 mm, P < 0.01) implied a downward movement of the hyoid bone. Compared with the treatment in the second group, orofacial myofunctional therapy combined with the preformed appliances led to a statistically significant lip strength increase (− 2.30, P < 0.05). Significant differences were observed in SNB and IMPA between the two groups (P < 0.05). Conclusions Orofacial myofunctional therapy effectively improved patient lip strength and was a good option for mixed dentition patients with lip incompetence. Preformed appliances could enhance the orofacial myofunctional therapy effect and result in significant improvements in lip strength and forward movement of the mandible, which can optimize the jaw relationship.